A new physical-cognitive scale for assessment of frailty in Chinese Han elderly. (3rd August 2019) - Li, Yan-Xun; Jiang, Xiao-Yan; Stone, Christopher; Ma, Ya-Jun; Liu, Qian; Hu, Zhi-Hao; Li, Xiao-Dong; Wang, Xiao-Feng; Li, Shu-Juan
ABSTRACT: Objective: To develop a physical- cognitive scale for assessment of frailty and compare the clinical features between the new scale and the conventional Fried criteria. Methods: 1757 individuals aged 70–84 were analyzed. Participants reporting three or more Fried phenotypes were grouped as frail patients (FP) whereas others as non-frail (NF). A score of Hasegawa's dementia scale (HDS-R) higher than 21.5 were classified as non-cognitive impairment group (NCI) group. By combining the cognitive and frailty criteria, participants manifesting three or more positive components out of the six were categorized into the Physical-cognitive frailty group (Pc-F) while others into non- Pc-F (Pc-NF). Results: Of all the participants, 46.7% (820) were males and 53.3% (937) were females. The mean age was 75.33 ± 3.90. 10.1% (178/1757) were evaluated as FP patients. The prevalence of CI was 53.2%; CI was much higher in the frail group (77.0%) than in the non-frail group (50.5%). Based on the new Pc-F scale, 163 out of 1579 NF participants were identified as Pc-F, and the prevalence of Pc-F reached 19.4% (341/1757). In the Pc-F group, there are more females, patients of advanced age, diabetes, stroke, CHD, CKD, metabolic syndrome, and high hs-CRP. Within the Pc-F group, patients with CI showed a higher incidence of exhaustion, low activity, weakness, and slowness than those without CI. Conclusions: Our study revealed a significantly worse status in frail participants with CI than without. Our new scale shows a stronger correlation between frailty and complications than the classic phenotype.